2012
DOI: 10.4103/2224-3151.207049
|View full text |Cite
|
Sign up to set email alerts
|

Challenges faced by skilled birth attendants in providing antenatal and intrapartum care in selected rural areas of Myanmar

Abstract: Heavy workload, geographical location, transportation and financial concerns were major challenges for SBAs, along with community compliance and mutual coordination. Good communication and service management skills were important to overcome these challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 2 publications
3
26
1
Order By: Relevance
“…Almost similar estimates were reported by previous studies done in Myanmar (more than 50%) and Laos (about 60%). 14,19 However, studies conducted in developed countries revealed lower proportions (4.4% to 27.3% % in USA, about 15% in UK and 41% in Australia) whereas some African studies reported comparable or higher values (53% in Ethiopia, 61.1% in Rwanda, 70.3% in Zambia, 81% in Nigeria, more than 70% in Tanzania and Malawi). 5,[16][17][18][20][21][22][23][24][25] Utilization of different cut-off points in defining late initiation of ANC could explain these discrepancies (first trimester or 12 completed weeks was used in USA and UK studies, 16 weeks in Ethiopian, Zambian, Tanzanian and Malawi studies, and second/third trimester in some studies).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Almost similar estimates were reported by previous studies done in Myanmar (more than 50%) and Laos (about 60%). 14,19 However, studies conducted in developed countries revealed lower proportions (4.4% to 27.3% % in USA, about 15% in UK and 41% in Australia) whereas some African studies reported comparable or higher values (53% in Ethiopia, 61.1% in Rwanda, 70.3% in Zambia, 81% in Nigeria, more than 70% in Tanzania and Malawi). 5,[16][17][18][20][21][22][23][24][25] Utilization of different cut-off points in defining late initiation of ANC could explain these discrepancies (first trimester or 12 completed weeks was used in USA and UK studies, 16 weeks in Ethiopian, Zambian, Tanzanian and Malawi studies, and second/third trimester in some studies).…”
Section: Discussionmentioning
confidence: 98%
“…27 However, a previous study conducted in Myanmar reported much lower gestational age at first ANC (15 weeks) while those detected in Ethiopian and Tanzanian studies were more than 20 weeks. 14,18,24 These discrepancies may be due to differences in time or site of study or differences in education and/or socioeconomic status among study population. Difference in culture or level of awareness on the significance of early initiation of ANC could explain these variations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concerning lack of the perceived value of antenatal care and its association with women's education, previously identified by [26] in a local study, remains to be an important and long-manifested barrier to the utilization of maternal health services in many low-income settings [27,28]. Coverage of essential antenatal care services received by the women was generally higher compared with available evidence from Myanmar (below 80%) [29]. However, high use of early antenatal care and low antenatal care attendance later during pregnancy is in contrast with other studies [26,30], suggesting an undesirable tendency.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies also showed that Traditional Birth Attendant (TBA) are seen as feasible and accessible at any time in the village compared to Community health facility [15,16,22]. In India, low utilization of SBA services occur due to poor quality services, unavailability and inaccessibility of services, minimum staff support, shortage of medicine and equipment as well as deficient referral systems [23].…”
Section: Discussionmentioning
confidence: 99%